ANALISA KINERJA SUMBER DAYA MANUSIA PADA PROYEK PEMBANGUNAN GEDUNG (Studi Kasus Pembangunan Gedung Poliklinik RSUD Dr.Abdoer Rahem Situbondo) - Zakariya, Hari; ., Suhartinah .; Manggala, Aditya Surya (HEXAGON, 2017)
The purpose of this study is to determine the feasibility of the work plan made by the owner of the project plan what is in accordance with the implementation of the building plan of clinic RSUD Dr. Abdoer Rahem Situbondo using effective labor management using AHSP made by the project owner with AHSP SNI to know the need of human resources (project workforce) used as a reference in the calculation of construction project resources in accordance with the condition of the building project of clinic RSUD Dr. Abdoer Rahem Situbondo.               From the results, implementation of the building project Polyclinic RS obtained network planning results work duration rill 132 working days with the difference of working days 33 days faster than the plan 165 working days. In the implementation of the project does not happen delays, only on the work process there is a non-significant but not resolved. Effective manpower management is done by recruiting a disciplined, experienced, skilled and responsible workforce on the job so that a good job is achieved. Comparison of AHSP contract and AHSP SNI obtained AHSP efficiency 62% contract and AHSP SNI 61% with difference of labor difference happened that is 552 labor. Where there are major jobs that experienced a considerable margin on the floor work and the wall of the crew were 637 workers. a significant difference between the workforce of the plan and the realization work on the RS polyclinic development project, which is seen in reinforced concrete work with 70% labor efficiency, wall work with 75% labor efficiency, and roof skeletal work with the level of energy efficiency 66% workforce.Keywords: Project Performance; Human Resources; AHSP